Evaluation of the Impact of the Stock Price on the Financial Performance of Telecommunication Companies in Zambia: A Case Study of Airtel Zambia Limited (2012 - 2021) - Mutafu, Wabei Catherine (International Journal of Finance, 2024)
Purpose: This paper evaluates the impact of the Lusaka Securities Exchange (LUSE) on the financial performance of telecommunication companies in Zambia: a study of Airtel Zambia Limited (2012 - 2021). Methodology: Using time series quantitative data and a combination of primary and secondary data obtained through structured questionnaires to meet the following specific research objectives: i) to analyse the effect of Airtel Zambia's stock price on the annual net revenue of Airtel Zambia, ii) to determine the correlation between Airtel Zambia's stock price and the annual net revenue of Airtel Zambia, iii) to determine management's level of knowledge of the Securities Exchange Market and how the knowledge is being applied to influence revenue performance, iv) to examine the perception of employees on the effect of stock price on the revenue performance of Airtel Zambia Limited and v) to identify and examine factors that affect revenue performance of Airtel Zambia Limited. Findings: The results of the study show that there exists a statistically significant relationship, there is a low effect of stock prices on Airtel Zambia's revenue and that there is a correlation between the stock price and revenue performance. This study underscores the need for increased participation in the Lusaka Securities Exchange (LUSE), improved branding and reputation management for listed companies, and further scholarly research in this field. Unique contribution to theory, policy and practice: It advocates for strategic initiatives by financial market players to stimulate market participation, and for companies to enhance their shareholder relations to potentially boost share prices and revenue. The study also identifies significant gaps in the literature, highlighting the opportunity for further research in this area.